To what extent does the DTI 'reward' and 'discipline' firms for performance and non-perfomance in target sectors? Industrial policy in South Africa's quest for a developmental state 1994-2013 - Johwa, Wilson (My University, 2016)
This dissertation delves into the contested post-1994 transition to deliver economic justice and development in South Africa, particularly the country’s more recent quest to emulate the interventionist economic strategies successfully implemented in South East Asia. It follows from the governing African National Congress (ANC) being one among a few governments that have explicitly committed themselves to building a developmental state. Among some of its intentions, such a state aims to alter market incentives, reduce risks, offer entrepreneurial visions and manage conflicts. Specifically, the research study examines the role of industrial sector planning in South Africa as a component of a developmental state. In the 20th century East Asian developmental states, also known as early generation developmental states, such selective industrial policy was characterised by close ties between government and business that facilitated the sharing of information. These countries – Japan, South Korea, Taiwan, Hong Kong and Singapore - were also distinguishable by the ability of the state to “discipline” capital through treating incentives, not as “gifts” but as enforceable performance contracts. The paper is split into three parts. Part 1 looks at the origins and evolution of the concept of a developmental state, along with key elements of such a state and their applicability to South Africa. Part 2 traces South Africa’s association with industrial sector planning, from the Jan Smuts era, through Hendrik Verwoerd until the Jacob Zuma administration. Part 3 is a case study that examines two particular sectors, the automotive industry and the business process outsourcing (BPO) sector (consisting of offshore call centres and related activities) to gauge the level of corporatism, along the state’s ability or desire to “discipline” or “reward” companies in pursuit of its industrialisation goals.
Research Report for the Degree of Master of Arts in Political Studies Graduate School for Humanities and Social Science University of the Witwatersrand Submitted: March, 2015
Keywords: South Africa. Department of Trade and Industry; Democracy--South Africa; Economic development--Political aspects; South Africa--Economic policy